Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004386.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for bacterial infections in afebrile neutropenic patients following chemotherapy

Abstract: Our review demonstrated that prophylaxis significantly reduced all-cause mortality. The most significant reduction in mortality was observed in trials assessing prophylaxis with quinolones. The benefit demonstrated in our review outweighs harm, such as adverse effects, and development of resistance, since all-cause mortality is reduced. Since most trials in our review were of patients with haematologic cancer, prophylaxis, preferably with a quinolone, should be considered for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 146 publications
2
78
1
2
Order By: Relevance
“…102 Since few studies have been performed in the last decade, an update of this meta-analysis did not report any significant changes. 103 Of note, 2 recent meta-analyses, one involving exclusively HSCT recipients (over 1400 patients, mostly after autologous HSCT) and the other including only randomized placebo-controlled and blinded studies failed to show significant survival benefit of FQ prophylaxis. 104,105 Moreover, there are growing concerns about a worldwide increase in resistance to FQs, and, consequently, the efficacy and ecological impact of FQ prophylaxis.…”
Section: Othersmentioning
confidence: 99%
“…102 Since few studies have been performed in the last decade, an update of this meta-analysis did not report any significant changes. 103 Of note, 2 recent meta-analyses, one involving exclusively HSCT recipients (over 1400 patients, mostly after autologous HSCT) and the other including only randomized placebo-controlled and blinded studies failed to show significant survival benefit of FQ prophylaxis. 104,105 Moreover, there are growing concerns about a worldwide increase in resistance to FQs, and, consequently, the efficacy and ecological impact of FQ prophylaxis.…”
Section: Othersmentioning
confidence: 99%
“…17 Although prophylaxis with quinolones exerts a significant selection pressure for colonization and infection by fluoroquinolone-resistant organisms, a recent Cochrane review confirmed earlier meta-analyses that the reduction in mortality and infection rates in high-risk patients still outweighs the risk of resistance, the costs and occasional adverse events. 22 Nevertheless, quinolone prophylaxis should be employed only in selected high-risk patients, not in all neutropenic patients. 12,17 4.…”
Section: This Issue Of Haematologica 21mentioning
confidence: 99%
“…9 Therefore, it seems reasonable to deduce the recommendations from the large number of randomized controlled clinical trials and the respective meta-analyses, which are available for other neutropenic conditions. [10][11][12][13][14][15] If the patient's condition allows (ECOG (Eastern Cooperative Oncology Group) performance status 0-2), the evaluation of patients with the possible diagnosis of AA can be performed as an outpatient.…”
Section: Prevention Of Infections By General Medical Management Of Aamentioning
confidence: 99%